Takeovers and Cooperatives - Frank Milne; David Kelsey (Queen's University, Department of Economics, 2006)
If consumers wholly or partially control a firm with market power they will charge less than the profit maximising price. Starting at the usual monopoly price, a small price reduction will have a second order effect on profits but a first order effect on consumer surplus. Despite this desirable static result, it has been argued that cooperatives are vulnerable to take-over by outsiders who will run them as for-profit businesses. This paper studies takeovers of cooperatives. We argue that cooperatives are in fact quite stable due to the Grossman-Hart problem of free riding during takeovers.
Keywords: D70; L20; 330; corporate governance; co-operative; take-over; free-rider; Corporate Governance; Übernahme; Unternehmenskooperation; Trittbrettfahrerverhalten; Externer Effekt; Theorie